Secondary Omental Torsion as a Rare Cause of Acute Abdomen in a Child and the Advantages of Laparoscopic Approach - Gargano, Tommaso; Maffi, Michela; Cantone, Noemi; Destro, Francesca; Lima, Mario (European Journal of Pediatric Surgery Reports, 2013)
Omental torsion is an underdiagnosed cause of acute abdomen in children. Most cases occur in adults, with only 15% presenting in children. It is estimated that omental infarct is found in approximately 0.1 to 0.5% of children undergoing operations for appendicitis. It may present with various signs and symptoms, although the clinical presentation usually mimics that of acute appendicitis. Definitive diagnosis is often established during surgery. We report a case of a 9-year-old boy who came to our attention for acute abdomen. We performed a laparoscopy-assisted procedure suspecting acute appendicitis. We therefore identified a secondary omental torsion associated with patency of the right inguinal duct and herniated omentum. Laparoscopy allowed a correct diagnosis and therapy.
Keywords: omental torsion; acute abdomen; laparoscopy